Dampak Implementasi Program Pembelajaran Merdeka Belajar Kampus Merdeka Pada Fakultas Ilmu Budaya Universitas Komputer Indonesia - Soni Mulyawan Setiana; Muhammad Rayhan Bustam; Mohammad Ali; Fenny Febrianty; Retno Purwani Sari (Universitas Komputer Indonesia, 2022)
This study aims to observe the impact of the implementation of MBKM learning program at the Faculty of Humanities, Universitas Komputer Indonesia (Unikom); In addition, this study also observes the understanding and interest of the students in the Faculty towards the program. This study uses a descriptive qualitative method, by taking data sources from the results of a questionnaire survey on the implementation of the MBKM program filled out by students of the Faculty; the questionnaire was facilitated by the Ministry of Education and Culture as the creator of the MBKM program. The results of this study indicate that students have positive perceptions regarding the implementation of MBKM Program learning activities. This is indicated by a good understanding of the program; also, it is indicated with a large enough interest to join the program, and the impact that is quite promising for the implementation of this program in the future for students of the Faculty. This research is expected to have a positive impact on improving the learning activities of tMBKM Program in the future, especially for its management at UNIKOM, especially at the Faculty of Humanities. Key Words : Impact, Faculty of Humanities, MBKM Program, Unikom